2019
DOI: 10.3390/ani10010075
|View full text |Cite
|
Sign up to set email alerts
|

The Overexpression of Tβ4 in the Hair Follicle Tissue of Alpas Cashmere Goats Increases Cashmere Yield and Promotes Hair Follicle Development

Abstract: Increased cashmere yield and improved quality are some goals of cashmere goat breeding. Thymosin beta-4 (Tβ4) plays a key role in the growth and development of hair follicles. For the past ten years, we have evaluated the role of Tβ4 by establishing a flock of 15 cashmere goats that specifically overexpress the Tβ4 gene in the hair follicles. These Tβ4 overexpression (Tβ4-OE) cashmere goats had more secondary hair follicles than the WT goats and produced more cashmere. Meanwhile, combined analysis of the skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…GLYATL2 is related to fat synthesis and it was significantly upregulated. KRT4 upregulation suggests significant increase in cell proliferation to promote SHF development and also increase cashmere yield [60]. Elevated expression of SLC1A2 suggests that it may promote hair growth and keratinocyte proliferation [61].…”
Section: Discussionmentioning
confidence: 99%
“…GLYATL2 is related to fat synthesis and it was significantly upregulated. KRT4 upregulation suggests significant increase in cell proliferation to promote SHF development and also increase cashmere yield [60]. Elevated expression of SLC1A2 suggests that it may promote hair growth and keratinocyte proliferation [61].…”
Section: Discussionmentioning
confidence: 99%
“…At present, studies have shown that Wnt, Shh, TGF-b, Notch, NF-kappa B, and PPAR signal pathways may be related to cashmere development [ 33 , 34 , 35 , 36 , 37 ]. In this study, we enriched six KEGG pathways in positive and negative modes, among which cholesterol metabolism, primary bile acid biosynthesis, and bile secretion were enriched in both ion modes ( Table 3 , 4).…”
Section: Discussionmentioning
confidence: 99%
“…The three pathways were annotated with four highly significant differences in metabolites: taurochenodeoxycholate, cholic acid, taurochenodeoxycholic acid, and glycochenodeoxycholic acid. Lactosylceramidase I in skin fibroblasts can be stimulated by pure taurocholate, while lactosylceramidase II can be stimulated by taurocholate or pure sugar deoxycholate, taurine deoxycholate, and taurine goose deoxycholate to catalyze the hydrolysis of lactose ceramide [ 33 ]. Cholesterol is crucial to the physiology of the skin and is a component of epidermal barrier function [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Inner Mongolian cashmere goat is an important source of germplasm with high economic value (Wu et al, 2020b). Cashmere is finer, stronger, lighter, and softer than wool, and it looks like a luxury fiber (Dai et al, 2019). Historically, wool played an important role in the economy of Portugal and Spain in the 15th century and Britain, Australia, and New Zealand since the beginning of the industrial revolution in the 18th century (Plowman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%